Pengaruh Penerapan Kebijakan Akuntansi terhadap Akuntabilitas dalam Mencegah Fraud pada Dinas Peternakan Bangkalan - Juniardi, Nadia Adisti Bernika; Fitri, Anis Lailatul; Fahmi, Rijal; Rijal, Syaifur; Djasuli, Mohamad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Transparency and fraud prevention are important principles in the financial system. This second principle guarantees legal certainty and increases the level of legitimacy in the decision-making process, because openness in the financial system becomes more expected by the public. Accountability and fraud prevention policies are very important for various organizations to have, especially public institutions today. One of the efforts made to create accountability and prevent fraud is through appropriate accounting policies. This research was conducted with a qualitative descriptive research design. The data collection method used in this research is semi-structured interviews and observation. The accounting policy implemented by the Bangkalan livestock service applies the principles of accountability, transparency and fraud prevention. It can be concluded that the accounting policy implemented by the Bangkalan livestock service has an effect on accountability and prevention. hoax.